Peningkatan Status Gizi Balita melalui Pelatihan PMT Berbasis Pangan Lokal pada Ibu Balita di Desa Katumbangan - Syamsidar Syamsidar; Adi Hermawan; Idawati Ambohamsah; Kamelia Kamelia (STIKES Marendeng Majene, 2026)
Nutritional problems among toddlers remain a challenge in Indonesia, including in Katumbangan Village, Polewali Mandar Regency, where cases of undernutrition and stunting are still prevalent. Utilizing local foods as complementary feeding (PMT) is considered important because they are nutritious, affordable, and easily available. This community service activity aimed to improve the knowledge and skills of mothers in preparing PMT based on local foods and to observe its impact on toddler nutritional status. A total of 30 mothers participated in activities including pre-test, counseling, demonstration, practice, and evaluation through post-test, observation, and monitoring of toddler nutritional status. Data were analyzed descriptively. Results showed an increase in the average knowledge score of mothers from 55.6 to 83.2, with 90% of mothers able to practice PMT preparation correctly. The nutritional status of toddlers also improved, with the proportion of well-nourished children (weight-for-age) increasing from 40% to 60%. It can be concluded that local food-based PMT training effectively improves mothers’ knowledge and skills and has a positive impact on toddler nutritional status. This program should be continued through integrated posyandu activities and multisectoral support as part of stunting prevention efforts.